"I Want It That Way": Enabling Interactive Decision Support Using Large Language Models and Constraint Programming - Lawless, Connor; Schoeffer, Jakob; Le, Lindy; Rowan, Kael; Sen, Shilad; Hill, Cristina St.; Suh, Jina; Sarrafzadeh, Bahar (ACM Transactions on Interactive Intelligent Systems, 2024)
A critical factor in the success of many decision support systems is the accurate modeling of user preferences. Psychology research has demonstrated that users often develop their preferences during the elicitation process, highlighting the pivotal role of system-user interaction in developing personalized systems. This paper introduces a novel approach, combining Large Language Models (LLMs) with Constraint Programming to facilitate interactive decision support. We study this hybrid framework through the lens of meeting scheduling, a time-consuming daily activity faced by a multitude of information workers. We conduct three studies to evaluate the novel framework, including a diary study to characterize contextual scheduling preferences, a quantitative evaluation of the system’s performance, and a user study to elicit insights with a technology probe that encapsulates our framework. Our work highlights the potential for a hybrid LLM and optimization approach for iterative preference elicitation, and suggests design considerations for building systems that support humansystem collaborative decision-making processes.